ARABICA AND ROBUSTA COFFEE PRODUCTION IN DIFFERENT GROWING ENVIRONMENTS ON THE SLOPES of MOUNT ARJUNA MALANG - Ari Wijayani; Sari Virgawati; Ninik Probosari (Jurnal Agrivet, 2021)
The area on the slopes of Mount Arjuna that has the potential to be developed as a center for Arjuna coffee is Toyomarto, which is located in Singosari District, Malang Regency at an altitude of 700-1400 meters above sea level. The types of coffee produced from the Toyomarto, Singosari plantations are Arabica and Robusta. The characteristics of the coffee have a sweet-sour character and a fruity aroma such as bananas, apples, and so on. The problem, in the field, shows that the low quality of coffee is due to the absence of standard methods of cultivation and post-harvest handling. At different altitudes, it shows differences in coffee production as well. The average productivity of Arabica coffee at an altitude of 1100 m above sea level is 55.97 tons, significantly different from coffee cultivated at an altitude below 1000 m above sea level. Meanwhile, Robusta coffee production is not significantly different at all altitudes where it is cultivated.